What does a graphical representation mean for students at the beginning of function teaching? - YAVUZ, İLYAS (My University, 2010)
This study examines how students in the early stages of learning about the concept of functions, describe a curve and, in particular, evaluate the appropriateness of their argument about the representation of a function. Students are offered a message game which is related to a curve drawn on a coordinate system, representing an 'imaginary function'. In this message game, one half of the class must describe a curve to the other half who will then try to reproduce it as similarly as possible. Data analysis indicates that the idea of the curve that consists of series of points is very effective, while the idea of variation does not exist or is too limited among students at the beginning of learning functions. Thus, the concept of variation is not used as a criterion to describe a curve. More surprisingly, the students are working on the curve as if it was just a picture on a grid regardless of the representation of the function. © 2010 Taylor & Francis.
Keywords: Didactic contract; Function; Graphical representation; Register of semiotic representation; Table of values